Kawasaki Disease: An Autopsy Case Series and Review of the Literature. (September 2016) - Chang, Hyemi Katherine; Fernandes, John; Nair, Vidhya
Abstract : Introduction: Kawasaki disease (KD) is a major cause of acquired heart disease in children, and there is limited information on postmortem findings in the pediatric population in Canada. Cases: For a 15-year time span (January 2000–March 2015), we had 2 cases of KD presented to the Department of Forensic Pathology at Hamilton General Hospital. Discussion: There were common cardiac findings including presence of giant coronary artery aneurysms and microscopic changes occurring within the coronary arteries and the myocardium. Evidence of old infarction was present in both heart specimens, but acute infarction was noted in one of the specimens. Conclusions: This case series documents postmortem findings that outline cardiac complications of KD including aneurysms, thrombotic events, and infarcts. In addition to addressing the medical complications of KD, it is also important to address the psychosocial effect due to its impact on quality of life.